Demographic factors, family background and prior self-employment on entrepreneurial intention: Vietnamese business students are different: Why? - Cuong Nguyen (Journal of Global Entrepreneurship Research, 2018)
This study investigates the impact of demographic factors, prior exposure to self-employment and family background on entrepreneurial intention of Vietnamese business students. Three hundred seventy-two undergraduate and post-graduate business students from three universities in Ho Chi Minh City completed a self-administered questionnaire which was analyzed through Independent Sample T-test and One-way ANOVA. Demographic factors include gender, age ranges and education level, family background include parents' employment status and parents' immigrant status. Results evidence somewhat higher entrepreneurial intention in male students. Furthermore, students whose parents are self-employed score higher entrepreneurial intention, but the difference is not statistically significant. The same is evidenced for students whose parents are immigrants from rural areas to urban cities versus non-immigrant parents. Prior experience in self-employment also increases entrepreneurial intention, albeit again insignificantly. Age and education levels show practically no impact. These results are in clear contradiction to the state with state of-the art international literature, which evidences significance in all these impact factors.
Keywords: 650; Entrepreneurial intention; Gender; Age; Education level; Prior experience in self-employment; Parent; Self-employed; Immigrant